Effects of emotional regulation and impulsivity on sports performance: the mediating role of gender and competition level - Millán-Sánchez, Antonio; Madinabeitia, Iker; de la Vega, Ricardo; Cárdenas, David; Ureña, Aurelio (Frontiers in Psychology, 2023)
Introduction This study aimed to study the relationships between emotional regulation and impulsivity on sports performance, according to the gender and competition level in national-level volleyball players. Methods In total, 77 players from the 2018–2019 top two Spanish divisions completed the ERQ (emotion regulation) and the UPPS-P (impulsivity). Statistics (serve, reception, and attack) were retrieved from the Spanish Volleyball Federation. A Mann–Whitney test was conducted to determine differences between gender and competition level in impulsivity and emotion regulation. A Kruskal–Wallis test (Mann–Whitney post-hoc) was carried out for playing positions analysis. Spearman's correlation was performed between the performance and the variables of impulsivity and emotional regulation. Results The results obtained, with differences according to playing position, gender, and competition level, show that players differ in certain psychological aspects that might influence how they approach their game. Discussion The results point in a promising direction: the sports practice analyzed can serve as a regulation context, for both the emotional response and the level of impulsivity of the players. The importance of these results for future research on this topic is discussed.